Linguistic Style Accommodation Shapes Impression Formation and Rapport in Computer-Mediated Communication - Muir, Kate; Joinson, Adam; Cotterill, Rachel; Dewdney, Nigel (Journal of language and social psychology, 2017)
Communication accommodation theory predicts that social power plays an important role in influencing communicative behaviors. Previous research suggests these effects extend to linguistic style, thought to be a nonconscious aspect of communication. Here, we explore if these effects hold when individuals converse using a medium limited in personal cues, computer-mediated communication. We manipulated social power in instant messaging conversations and measured subsequent interpersonal impressions. Low power induced greater likelihood of linguistic style accommodation, across between- (Study 1) and within-subjects (Study 2) experiments. Accommodation by those in a low-power role had no impact on impressions formed by their partner. In contrast, linguistic style accommodation by individuals in a high-power role was associated with negative interpersonal impressions formed by their lower power partner. The results show robust effects of power in shaping language use across computer-mediated communication. Furthermore, the interpersonal effects of linguistic accommodation depend on the conversational norms of the social context.